A Prospective, Randomized Trial of Intravenous Hydroxocobalamin Versus Whole Blood Transfusion Compared to No Treatment for Class III Hemorrhagic Shock Resuscitation in a Prehospital Swine Model. (2nd March 2015) - Bebarta, Vikhyat S.; Garrett, Normalynn; Boudreau, Susan; Castaneda, Maria; O'Neil, Brian
Abstract Objectives The objective was to compare systolic blood pressure (sBP) over time in swine that have had 30% of their blood volume removed (Class III shock) and treated with intravenous (IV) whole blood or IV hydroxocobalamin, compared to nontreated control animals. Methods Thirty swine (45 to 55 kg) were anesthetized, intubated, and instrumented with continuous femoral and pulmonary artery pressure monitoring. Animals were hemorrhaged a total of 20 mL/kg over a 20‐minute period. Five minutes after hemorrhage, animals were randomly assigned to receive 150 mg/kg IV hydroxocobalamin solubilized in 180 mL of saline, 500 mL of whole blood, or no treatment. Animals were monitored for 60 minutes thereafter. A sample size of 10 animals per group was determined based on a power of 80% and an alpha of 0.05 to detect an effect size of at least a 0.25 difference (>1 standard deviation) in mean sBP between groups. sBP values were analyzed using repeated‐measures analysis of variance (RANOVA). Secondary outcome data were analyzed using repeated‐measures multivariate analysis of variance (RMANOVA). Results There were no significant differences between hemodynamic parameters of IV hydroxocobalamin versus whole blood versus control group at baseline (MANOVA; Wilks' lambda; p = 0.868) or immediately posthemorrhage (mean sBP = 47 mm Hg vs. 41 mm Hg vs. 37 mm Hg; mean arterial pressure = 39 mm Hg vs. 28 mm Hg vs. 34 mm Hg; mean serum lactate = 1.2 mmol/L vs. 1.4 mmol/L vs. 1.4 mmol/L; MANOVA; Wilks' lambda; p = 0.348). The outcome RANOVA model detected a significant difference by time between groups (p < 0.001). Specifically, 10 minutes after treatment, treated animals showed a significant increase in mean sBP compared to nontreated animals (mean sBP = 76.3 mm Hg vs. 85.7 mm Hg vs. 51.1 mm Hg; p < 0.001). RMANOVA modeling of the secondary data detected a significant difference in mean arterial pressure, heart rate, and serum lactate (p < 0.001). Similar to sBP, 10 minutes after treatment, treated animals showed a significant increase in mean arterial pressure compared to nontreated animals (mean arterial pressure = 67.7 mm Hg vs. 61.4 mm Hg vs. 40.5 mm Hg). By 10 minutes, mean heart rate was significantly slower in treated animals compared to nontreated animals (mean heart rate = 97.3 beats/min vs. 95.2 beats/min vs. 129.5 beats/min; p < 0.05). Serum lactate, an early predictor of shock, continued to rise in the control group, whereas it did not in treated animals. Thirty minutes after treatment, serum lactate values of treated animals were significantly lower compared to nontreated animals (p < 0.05). This trend continued throughout the 60‐minute observation period such that 60‐minute values for lactate were 1.4 mmol/L versus 1.1 mmol/L versus 3.8 mmol/L. IV hydroxocobalamin produced a statistically significant increase in systemic vascular resistance compared to control, but not whole blood, with a concomitant decrease in cardiac output. Conclusions Intravenous hydroxocobalamin was more effective than no treatment and as effective as whole blood transfusion, in reversing hypotension and inhibiting rises in serum lactate in this prehospital, controlled, Class III swine hemorrhage model.